Enamel remineralization by fluoride-releasing materials: Proposal of a pH-cycling model - Rodrigues, Eliana [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pedrini, Denise [UNESP]; Cavassan, Luciana [UNESP] (FapUNIFESP (SciELO), 2010)
This study proposes a pH-cycling model for verifying the dose-response relationship in fluoride-releasing materials on remineralization in vitro. Sixty bovine enamel blocks were selected for the surface microhardness test (SMH 1). Artificial caries lesions were induced and surface microhardness test (SMH 2) was performed. Forty-eight specimens were prepared with Z 100, Fluroshield, Vitremer and Vitremer 1/4 diluted - powder/liquid, and subjected to a pH-cycling model to promote remineralization. After pH-cycling, final surface microhardness (SMH 3) was assessed to calculate percent recovery of surface microhardness (%SMH R). Fluoride present in enamel (μg F/mm 3) and in the pH-cycling solutions (μg F) was measured. Cross-sectional microhardness was used to calculate mineral content (ΔZ). There was no significant difference between Z 100 and control groups on analysis performed on - %SMH R, ΔZ, μ F and μ F/mm 3 (p>0.05). Results showed a positive correlation between %SMH R and μg F/mm 3 (r=0.9770; p=0.004), %SMH R and μg F (r=0.9939; p=0.0000001), DZ and μg F/mm 3 (r=0.9853; p=0.0002), ΔZ and μg F (r=0.9975; p=0.0000001) and between μg F/mm 3 and μg F (r=0.9819; p=0.001). The pH-cycling model proposed was able to verify in vitro dose-response relationship of fluoride-releasing materials on remineralization.
Keywords: Dental materials; Fluoride; Tooth remineralization; anticaries agent; biomedical and dental materials; bisphenol A bis(2 hydroxypropyl) ether dimethacrylate; fissure sealant; fluoride; Fluoroshield; glass ionomer; mineral; polyurethan; resin; silicon dioxide; Vitremer; Z100 composite resin; zirconium; animal; cattle; chemistry; dental care; dental caries; dose response; drug effect; enamel; hardness; methodology; pathology; pathophysiology; pH; tooth disease; Animals; Bisphenol A-Glycidyl Methacrylate; Cariostatic Agents; Cattle; Composite Resins; Dental Caries; Dental Enamel; Dental Materials; Dose-Response Relationship, Drug; Fluorides; Glass Ionomer Cements; Hardness; Hydrogen-Ion Concentration; Minerals; Pit and Fissure Sealants; Polyurethanes; Silicon Dioxide; Tooth Demineralization; Tooth Remineralization; Zirconium